(untitled) - Breasted, James Henry ([Boston], 1944)
This Second Edition, to begin the human career with the Early Stone Age entirely surrounding the Mediterranean, including the Near East, and then to continue it in chronological sequence down through the origins of civilization and the subsequent developments of civilized life in the Near East alone, to the point when these influences passed over into Europe. Besides presenting new facts, these recent discoveries have contributed especially to the new series of illustrations in this volume. As a result of all these discoveries, the account of the history of civilization preceding the Greeks and the Romans has been entirely rewritten, making this edition practically a new book. The material has been divided into five main sections: Man before Civilization ~ The Origins and Early History of Civilization in the Ancient Near East ~ The Greeks ~ The Mediterranean World in the Hellenistic Age and the Roman Republic ~ The Roman Empire. Illustrated with Maps and Colored Plates.
Keywords: History, Ancient,Lịch sử, cổ đại